the Effect of Age and Height on Some Selected Physical Properties of Ethiopian Highland Bamboo (Yushania Alpina) - Girma, Yohannis gebremariam; Assefa, Dessie (International Journal of Scientific Research and Management (IJSRM), 2018)
Ethiopian highland bamboo is a multipurpose and a fast growing plant that supports local livelihoods in many ways. It is a source of food, fodder, furniture, textile raw material, building material, industrial inputs, fuel and other purposes in Ethiopia. Physical properties are considered to be important factors in determining the suitability of bamboo for various applications. A sufficient knowledge of the physical properties of bamboo ensures safe design for materials used in service.  In this study, Effects of age and height on the basic density, moisture content, wall thickness and culm diameter of Ethiopian highland bamboo (Yushinia alpina) were studied on 2, 3 and 4 years-old bamboo. The result of the study show that four years old bamboo had the highest moisture content and wall thickness and the lowest density and culm diameter. Density and culm diameter did not show significant difference between 2, 3, and 4 years of old bamboo. However, variation in moisture content and wall thickness were observed between the three age groups. Density had greatest in bottom and lowest, in the top. There is no variation of moisture content, wall thickness and culm diameter at different height positions (Bottom, Middle and Top).